TURBINE DISK PROFILE OPTIMIZATION APPLYING DESIGN OF EXPERIMENT AND RESPONSE SURFACE METHOD - ZHANG ZhiYi; LIU Yang; PI ZiZi; DENG XiaoTao; DENG YiTai (Jixie qiangdu)
Profile of a turbine disk was optimized in ANSYS Workbench platform and results suggested that disk stresses were decreased significantly while the disk mass was lightened as well. Present research demonstrates that ANSYS Workbench platform integrating geometry modeling,stress analysis and optimization module can minimize the difficulties of optimization work,the accuracy of surrogate model using Design of Experiments（ DOE） and Response Surface Method（ RSM） can satisfy engineering requirements and the application of combination optimization strategy involving DOE,RSM and Multi-Objective Genetic Algorithm（ MOGA） can obviously enhance the optimization efficiency.